Analisis Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah ( SAK EMKM ) Dalam Penyusunan Laporan Keuangan Pada Bakpia Gading Banyakan Kab. Kediri - Munica Putri Jion Viarma; Akhmad Naruli; Putri Awalina (Jurnal Riset Rumpun Ilmu Ekonomi, 2024)
Micro, small and medium enterprises (MSMEs) usually carry out financial recording and reporting in a simple manner, which is not in accordance with applicable financial reporting standards. This can mislead users of financial reports. The preparation of financial reports using Financial Accounting Standards (SAK) for MSMEs is expected to provide clear guidelines in recording and presenting MSME financial reports. The aim of this research is to find out how SAK EMKM is applied to company financial reports (Case Study of Bakpia Gading Kediri). This research is a quantitative descriptive research on the application of SAK EMKM to financial reports at Bakpia Gading Kediri with a research time limit of 1 month in January 2022. The data source in this research is primary data obtained from the company directly. Data collection techniques are carried out through interviews and documentation. The data analysis technique in this research is quantitative descriptive. The results of the research show that Bakpia Gading in preparing financial reports has not implemented or used financial reporting guidelines that are in accordance with the applicable SAK EMKM, the company only prepared very simple reports.